AUTONOMY AND MORPHOLOGICAL PROFILE OF ELDERLY RELIGIOUS PEOPLE OF JACAREPAGUÁ (Fiep Bulletin - online, 2012)
Aging can be characterized by the gradual loss of the body's ability to maintain homeostasis (Farinati, 2008). According to WHO (2001), population aging is occurring worldwide, causing individuals aged 60 years or more to reach the amount of one billion two hundred million people around the world in the year 2025 (WHO, 2001). O processo de envelhecimento acompanha diversas alterações fisiológicas, relativas às funções cardiorrespiratória e neuromuscular e à composição corporal (TORTORA, GRABOWSKI, 2002). Regular physical activity provides health benefits, for example, reducing the risk of cardiovascular disease, type II diabetes and osteoporosis, as well as aid in weight control and promoting psychological well-being (WHO, 2010; MacArdle et al, 1999). The objective of this study is to correlate age and morphological profile with the autonomy of elderly patrons of the Third Age Pastoral Jacarepaguá (RJ). A descriptive, quantitative and qualitative character, sought to profile and morphology of the autonomy of elderly 36. The 36 participants had average WHR 0.86 + 0.06 + 3.56 BMI of 28.14, ranking the group of overweight participants. When performing tests of autonomy GDLAN protocol, the participants reached the following results: C10M to an average of 7.17 + 1.51 seconds; LPS in a time of 11.86 + 3.37 seconds and VTC average obtained was 12.10 + 4.05 seconds. The data showed that the group was in a range of risk for disease and their assessments of functional autonomy demonstrated difficulty in performing simple movements of the day to day. Greater attention may be needed for individuals of student age for health promotion and performance of activities of daily habit.
Keywords: Physical activity; functional autonomy; morphological profile